Hardiness and Outcome of Self-catheterisation Training (HOST): protocol for an observational study exploring the effects of personality traits in women on ability to learn clean intermittent self-catheterisation. Issue 1 (8th January 2014) - Perkins, Kalbinder; Randall, Duncan; Toozs-Hobson, Philip; Sitch, Alice; Ismail, Khaled MK
Abstract : Introduction: Clean intermittent self-catheterisation (CISC) is the recommended first-line management of voiding dysfunction; however, psychological factors involved in acceptance and take up are often neglected. There is a tendency to discuss the success of CISC in relation to factors that affect teaching and learning, with subsequent success or failure being attributed to these. There is limited research investigating what extent, personality traits impact on a woman's willingness to learn CISC and subsequent mastery of the technique. Method and analysis: All women attending a tertiary urogynaecology department as eligible for CISC will be invited to participate in the study. Over the 14-month recruitment period, an estimated 130 women will be involved. The participants will complete a series of self-reported questionnaires. Personality types will be assessed using The Hardiness Scale and State-Trait Anxiety Inventory. The impact of urinary symptoms and CISC on quality of life (QoL) will be measured using an electronic pelvic-floor assessment questionnaire (ePAQ). Success and mastery will be measured by recording the number of hospital appointments and the length of time taken to learn. Confidence will be measured using the Likert scale. A sample of 20 women will be invited to participate in semi-structured in-depth interviews to explore women's views and experiences of CISC. Ethics and dissemination: Regulatory approvals will be in place prior to the start of the study. Good clinical practice guidelines will be followed throughout. Eligibility and training for CISC will be undertaken in accordance to individualised care plans in line with unit protocol and will not be influenced by the study. Trial data will be anonymised and participant confidentiality will be maintained. The Study findings will be disseminated through publications in relevant journals and will be presented at multiprofessional conferences and scientific meetings.